Skeletal Muscle Pyruvate Dehydrogenase Phosphorylation and Lactate Accumulation During Sprint Exercise in Normoxia and Severe Acute Hypoxia: Effects of Antioxidants - Morales-Alamo, David (Front Physiol, 2018)
Compared to normoxia, during sprint exercise in severe acute hypoxia the glycolytic rate is increased leading to greater lactate accumulation, acidification, and oxidative stress. To determine the role played by pyruvate dehydrogenase (PDH) activation and reactive nitrogen and oxygen species (RNOS) in muscle lactate accumulation, nine volunteers performed a single 30-s sprint (Wingate test) on four occasions: two after the ingestion of placebo and another two following the intake of antioxidants, while breathing either hypoxic gas (P(I)O(2) = 75 mmHg) or room air (P(I)O(2) = 143 mmHg). Vastus lateralis muscle biopsies were obtained before, immediately after, 30 and 120 min post-sprint. Antioxidants reduced the glycolytic rate without altering performance or VO(2). Immediately after the sprints, Ser(293)- and Ser(300)-PDH-E1α phosphorylations were reduced to similar levels in all conditions (~66 and 91%, respectively). However, 30 min into recovery Ser(293)-PDH-E1α phosphorylation reached pre-exercise values while Ser(300)-PDH-E1α was still reduced by 44%. Thirty minutes after the sprint Ser(293)-PDH-E1α phosphorylation was greater with antioxidants, resulting in 74% higher muscle lactate concentration. Changes in Ser(293) and Ser(300)-PDH-E1α phosphorylation from pre to immediately after the sprints were linearly related after placebo (r = 0.74, P < 0.001; n = 18), but not after antioxidants ingestion (r = 0.35, P = 0.15). In summary, lactate accumulation during sprint exercise in severe acute hypoxia is not caused by a reduced activation of the PDH. The ingestion of antioxidants is associated with increased PDH re-phosphorylation and slower elimination of muscle lactate during the recovery period. Ser(293) re-phosphorylates at a faster rate than Ser(300)-PDH-E1α during the recovery period, suggesting slightly different regulatory mechanisms.